Architectures d’autoroutes - Verdiana Peron (In Situ)
Nowadays, the facilities of large-scale infrastructures are subject to unprecedented preservation challenges. The protection of these buildings requires an innovative approach. This will be possible through the establishment of new public policies that acknowledge them as part of Italy’s 20th century cultural heritage. The Italian motorway service chain was a unique project in Europe. It was an emblem of a new post-war national identity as well as a symbol of architectural and engineering experimentation. These buildings (1958-1972) are currently threatened by invasive interventions, caused by a lack of recognition of their cultural value. This study compares, for the first time, the original features of motorway restaurants with the current situation. The majority of the original buildings have been demolished or significantly altered. This paper examines three case studies: the rest-stops in Novara, Soave, and Lainate. Additionally, it highlights the link between the recognition of the cultural value and subsequent operational practices, as well as the positions of stakeholders. Moreover, the essay provides new insights into the stance of public policies and preservation procedures. The connection between knowledge and enhancement of these buildings is the key point of the research. Its final aim is to give theoretical tools and methods to guide future interventions on such heritage.